The biogeography of pierids butterflies (Lepidoptera: Pieridae) in Potohar region of Pakistan. (3rd April 2017) - Shah, Syed Waqar; Rafi, Muhammad Ather; Zia, Ahmed; Sultana, Riffat
Abstract: From Potohar region of Pakistan pierids butterflies and their biogeographical affiliation were studied during January 2012–February 2015. Of the species found, 10 namely ( Delias eucharis, Pontia daplidice, Anaphaeis aurota, Belenois aurota, Pieris rapae, Pieris canidia, Pieris brassicae, Ixias pyrene, Colotis amata, Colotis etrida and Colotis protractus ) belonged to subfamily Pierinae, while subfamily Coliadinae represented seven species i.e. ( Catopsilia pyranthe, Catopsilia pomona, Gonepteryx nepalensis, Colias fieldii, Colias erate, Eurema laeta, and Eurema hecabe. ) Out of 17 reported species, 5 ( Colotis amata, Colotis etrida, Colotis protractus Anaphaeis aurota = Belenois aurota and Delias eucharis ) species were new records for the pierid fauna of Potohar region. However, one species i.e . Gonepteryx nepalensis was already recorded from Pakistan as G. mahaguru or G. rhamni (wrong determination). Biogeographical affiliations of pierids butterflies in Potohar region indicated that pierid fauna of this region is affiliated with four biogeographical regions except to the Nearctic Neotropical region. The Oriental and Palearctic are dominant. However, the Afrotropical and the Australian elements are also present with good representation.